Enantioselective Total Synthesis of (+)‐Steenkrotin A and Determination of Its Absolute Configuration. Issue 3 (11th December 2015) - Pan, Saiyong; Gao, Beiling; Hu, Jialei; Xuan, Jun; Xie, Hujun; Ding, Hanfeng
Abstract: The first enantioselective total synthesis of (+)‐steenkrotin A has been achieved in 18 steps and 4.2 % overall yield. The key features of the strategy entail a Rh‐catalyzed O−H bond insertion followed by an intramolecular carbonyl‐ene reaction, two sequential SmI2 ‐mediated Ueno–Stork and ketyl–olefin cyclizations, and a cascade intramolecular aldol condensation/vinylogous retro‐aldol/aldol process with inversion of the relative configuration at the C7 position. The absolute configuration of (+)‐steenkrotin A was determined based on the stepwise construction of the stereocenters during the total synthesis. Abstract : Riding the tricycle : A concise and enantioselective total synthesis of (+)‐steenkrotin A is reported (see scheme). The key steps include a rhodium carbenoid O−H insertion followed by a carbonyl‐ene reaction, two sequential SmI2 ‐mediated Ueno–Stork and ketyl–olefin cyclizations, and a cascade intramolecular aldol condensation/vinylogous retro‐aldol/aldol process. The absolute configuration of (+)‐steenkrotin A was determined based on the stepwise construction of the stereocenters during the synthesis.